2022
DOI: 10.1186/s12935-021-02407-8
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with immune checkpoint inhibitors (ICIs); a new frontier

Abstract: Recently, immune checkpoint inhibitors (ICIs) therapy has become a promising therapeutic strategy with encouraging therapeutic outcomes due to their durable anti-tumor effects. Though, tumor inherent or acquired resistance to ICIs accompanied with treatment-related toxicities hamper their clinical utility. Overall, about 60–70% of patients (e.g., melanoma and lung cancer) who received ICIs show no objective response to intervention. The resistance to ICIs mainly caused by alterations in the tumor microenvironm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(92 citation statements)
references
References 312 publications
(271 reference statements)
0
69
0
Order By: Relevance
“…Immune checkpoint inhibitors (ICIs), represented by cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) inhibitors, programmed cell death protein 1 (PD-1) inhibitors, and programmed cell death protein ligand 1 (PD-L1) inhibitors, have transformed cancer treatment since ipilimumab was first approved for melanoma in 2011 (1). ICIs bring lasting objective remission to patients with cancer by activating autologous lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Immune checkpoint inhibitors (ICIs), represented by cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) inhibitors, programmed cell death protein 1 (PD-1) inhibitors, and programmed cell death protein ligand 1 (PD-L1) inhibitors, have transformed cancer treatment since ipilimumab was first approved for melanoma in 2011 (1). ICIs bring lasting objective remission to patients with cancer by activating autologous lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have examined staggered dosing of these agents and many have demonstrated that timing of checkpoint inhibition is critical [60,61]. Other studies have also demonstrated that the benefits of immune checkpoint inhibition used in conjunction with chemotherapy occur at specific dose ranges [62,63]. Additionally, it is important to note that divergent tumor biology may contribute to conflicting Th1/Th2 cytokine profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, targeting several processes in cancer cells may increase the therapeutic e ciency of therapy. For this reason, combination therapy has been shown an effective antitumor response rather than monotherapy [32]. Currently, the reports of various research show that despite the robust results of chemoimmunotherapy in comparison with chemotherapy alone, it has not improved outcomes in patients [33].…”
Section: Discussionmentioning
confidence: 99%